2018
DOI: 10.1021/acsomega.8b01478
|View full text |Cite
|
Sign up to set email alerts
|

Improved Admixture Vaccine of Fentanyl and Heroin Hapten Immunoconjugates: Antinociceptive Evaluation of Fentanyl-Contaminated Heroin

Abstract: Fentanyl and its derivatives have become pervasive contaminants in the U.S. heroin supply. Previously, we reported a proof-of-concept vaccine designed to combat against heroin contaminated with fentanyl. Herein, we optimized the admixture vaccine and found that it surpassed the individual vaccines in every antinociceptive test, including a 10% fentanyl to heroin formulation. It is anticipated that other co-occurring drug abuse disorders may also be examined with admixture vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 26 publications
5
38
0
Order By: Relevance
“…Maximum antinociceptive potency shifts following vaccine administration were approximately 3-and 5-fold for IV and SC heroin, respectively and lasted for at least seven-toeight weeks. The present results are consistent with previous heroin conjugate vaccine studies in male and female mice (Bremer et al, 2017;Bremer et al, 2014;Hwang et al, 2018a;Hwang et al, 2018b;Hwang et al, 2018c;Jalah et al, 2015;Matyas et al, 2014;Sulima et al, 2017) and Schwienteck 15 male rats (Schlosburg et al, 2013;Stowe et al, 2011;Sulima et al, 2017). The present results extended these previous findings to the inclusion of female rats and no sex difference in vaccine effectiveness was observed.…”
Section: Schwienteck 14supporting
confidence: 93%
See 3 more Smart Citations
“…Maximum antinociceptive potency shifts following vaccine administration were approximately 3-and 5-fold for IV and SC heroin, respectively and lasted for at least seven-toeight weeks. The present results are consistent with previous heroin conjugate vaccine studies in male and female mice (Bremer et al, 2017;Bremer et al, 2014;Hwang et al, 2018a;Hwang et al, 2018b;Hwang et al, 2018c;Jalah et al, 2015;Matyas et al, 2014;Sulima et al, 2017) and Schwienteck 15 male rats (Schlosburg et al, 2013;Stowe et al, 2011;Sulima et al, 2017). The present results extended these previous findings to the inclusion of female rats and no sex difference in vaccine effectiveness was observed.…”
Section: Schwienteck 14supporting
confidence: 93%
“…In addition, midpoint antibody titer levels in the present study were comparable to previous levels in mice (Bremer et al, 2017). The magnitude of heroin vaccineinduced potency shifts was similar to previous heroin-TT conjugate vaccine results using schedule-controlled responding in nonhuman primates (4-fold) and antinociceptive effects in female mice (5-7 fold) for heroin administered intramuscular (IM) and IP, respectively (Bremer et al, 2017;Hwang et al, 2018b;Hwang et al, 2018c). However, heroin potency shifts observed in the present study following heroin vaccine administration were less previously reported antinociceptive potency shifts (12-14 fold) in male mice administered heroin SC and IP (Bremer et al, 2017).…”
Section: Schwienteck 14supporting
confidence: 88%
See 2 more Smart Citations
“…Yet, this same fentanyl vaccine elicited antibodies displaying very weak affinity towards structurally dissimilar opioids such as heroin (Bremer et al, 2016;Hwang et al, 2018a). Recent preclinical research has explored the development of combination immunopharmacotherapy approaches directed at multiple, structurally dissimilar abused opioids (e.g., fentanyl and heroin) (Hwang et al, 2018b;Hwang et al, 2018c). In conclusion, opioid-targeted vaccines may provide for a unique clinically effective option for OUD treatment.…”
Section: Fentanyl Vaccine In Nhps 16mentioning
confidence: 99%